ИСТОРИКО-ГЕОГРАФИЧЕСКАЯ СЕМАНТИКА ТОПОНИМОВ В ЭПОСЕ «КИТАБИ-ДЕДЕ КОРКУТ» (Eurasian Journal of Philology Science and Education, 2015)
Toponyms reflect life and people history. In this sense the toponymy of the epos «Kitabi-Dede Korkut» is the basic means for definition of a place of stay mentioned in it oghuz people. Having paid attention to the monument text, we see that the oghuz edge was established on the big space.